Migration across three continents : the d’Angelis family - Antonella Viola (Conserveries Mémorielles)
The article deals with the long migration of an Italian family. Its main aim is to unveil hidden links between migration, memory and the formation of a cultural identity highly influenced by personal re-elaborations of the family’s Italian origin. The process of migration has been elaborated by many family members in a peculiar way ; they have constructed their own memory using a wide-range of real and fictive elements which helped them make sense of long and unusual migration. A family memory based on personal recollections and elements deriving from the family’s past -re-articulated according to specific individual needs. This family memory influenced the formation of a mixed cultural identity within which Italianess is considered as a distinctive feature of the family’s background. By analyzing the experience of the D’Angelis family, the article provides new insights into how people of mixed cultural heritage feel and interpret migration through the sieve of memory and construct their own specific identitary models.